MKP1 phosphatase is recruited by CXCL12 in glioblastoma cells and plays a role in DNA strand breaks repair. (31st August 2019) - Dedobbeleer, Matthias; Willems, Estelle; Lambert, Jeremy; Lombard, Arnaud; Digregorio, Marina; Lumapat, Paul Noel; Di Valentin, Emmanuel; Freeman, Stephen; Goffart, Nicolas; Scholtes, Felix; Rogister, Bernard
Abstract: Glioblastoma (GBM) is the most frequent and aggressive primary tumor in the central nervous system. Previously, the secretion of CXCL12 in the brain subventricular zones has been shown to attract GBM cells and protect against irradiation. However, the exact molecular mechanism behind this radioprotection is still unknown. Here, we demonstrate that CXCL12 modulates the phosphorylation of MAP kinases and their regulator, the nuclear MAP kinase phosphatase 1 (MKP1). We further show that MKP1 is able to decrease GBM cell death and promote DNA repair after irradiation by regulating major apoptotic players, such as Jun-N-terminal kinase, and by stabilizing the DNA repair protein RAD51. Increases in MKP1 levels caused by different corticoid treatments should be reexamined for GBM patients, particularly during their radiotherapy sessions, in order to prevent or to delay the relapses of this tumor. Abstract : We demonstrated in this study that the nuclear phosphatase MKP1 (MAP kinase phosphatase 1), upon its phosphorylation by a CXCL12 stimulation, directly participates in the DNA strand breaks repair in irradiated glioblastoma (GBM) cells. Moreover, this phosphatase indirectly promotes GBM cells survival after irradiation.